The Influence Of Supervision And Work Discipline On Employee Performance At The Lungkang Kule Sub-District Office, Kaur District - Heryanti, Neli; Susanti, Neri; Herlina, Yeni (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
The purpose of this study was to determine the effect of supervision and work discipline on the performance of employees at the Lungkang Kule District Office, Kaur Regency. The population in this study were all employees at the Lungkang Kule District Office, Kaur Regency, totaling 31 employees, with a sample size of 31 employees. The sampling technique was cluster sampling. The data analysis technique used multiple linear regression: Y = 23.319 + 0.166X1 + 0.015X2, meaning that if supervision and work discipline were increased by 100%, employee performance would be worth 0.166 and 0.015 respectively. The results of the study showed simultaneously by comparing the F count value with F table, so that it was known that the F table value was 3.757 > 3.16 and it could be concluded that supervision and work discipline had a significant effect on employee performance at the Lungkang Kule District Office, Kaur Regency. Based on the partial test, it is known that supervision has a positive and significant effect on the performance of employees at the Lungkang Kule District Office, Kaur Regency with a sig value of 0.004 < alpha (0.05), while work discipline has a positive and insignificant effect on the performance of the Lungkang Kule District Office, Kaur Regency with a sig value of 0.810 > alpha (0.05).